Light‐Controlled Interconversion between a Self‐Assembled Triangle and a Rhombicuboctahedral Sphere. Issue 1 (26th November 2015) - Han, Muxin; Luo, Yuansu; Damaschke, Bernd; Gómez, Laura; Ribas, Xavi; Jose, Anex; Peretzki, Patrick; Seibt, Michael; Clever, Guido H.
Abstract: Stimuli‐responsive structural reorganizations play an important role in biological processes, often in combination with kinetic control scenarios. In supramolecular mimics of such systems, light has been established as the perfect external trigger. Here, we report on the light‐driven structural rearrangement of a small, self‐assembled Pd3 L6 ring based on photochromic dithienylethene (DTE) ligands into a rhombicuboctahedral Pd24 L48 sphere measuring about 6.4 nm across. When the wavelength is changed, this interconversion can be fully reversed, as confirmed by NMR and UV/Vis spectroscopy as well as mass spectrometry. The sphere was visualized by AFM, TEM, and GISAXS measurements. Due to dissimilarities in the photoswitch conformations, the interconversion rates between the two assemblies are drastically different in the two directions. Abstract : Lights, action! Irradiation with light of different wavelengths triggers the reversible conversion of small, self‐assembled Pd3 L6 rings based on photochromic dithienylethene ligands into rhombicuboctahedral Pd24 L48 spheres measuring 7 nm across.